A study conducted proficiency testing of laboratory test for the compression strength of corrugated fiberboard boxes - Chaisanit, Jierasak; Phanphang, Suradej; Somboon, Kwanjai; Tuchinda, Poovadee (Bulletin of Applied Sciences, 2022)
This project was researching test results in corrugated fiberboard boxes from industry. The objective of this project was to comply testing information on compression strength of corrugated fiberboard boxes to use as a guideline to conducted proficiency testing. The information was obtained by delivering the prepared samples to 26 industrial laboratories. The testing results were analyzed by robust Z-score and relative standard deviation methods following ISO 13528: 2015. It was found that the testing results of 23 laboratories were satisfactory (|Z| 2.0), of 2 laboratories were questionable (2<|z|< 3) and of 1 laboratory was unsatisfactory (|z| 3). The normal distribution of z-score was considered well-established and the proficiency testing could use these 3 criterions. The repeatability of these results was then analyzed with %RSD method. It was found that the results from 17 laboratories was acceptable and from 9 laboratories was unacceptable. This was because the laboratories were not under control conditions, the equipment was older than 15 years and laboratories were not certified ISO 17025. The laboratories were advised to improve on performances for the proficiency testing in the future.